A Practical Guide on Computational Tools and Databases for Transposable Elements in Plants - Oliveira, Liliane Santana; de Amorim, Tharcísio Soares; Pedro, Daniel Longhi Fernandes; da Rocha Vicente, Fábio Fernandes; Paschoal, Alexandre Rossi (Methods in molecular biology (Clifton, N.J.), 2021)
In the age of big data, obtaining precise information about the research topic of interesting is extremely important. Keeping this in mind, this chapter focuses on providing a practical knowledge guide about computational tools and databases of transposable elements (TE) in plants. For that, we organize and present this text in three sections: (1) a discussion about tools and databases on this theme; (2) hands-on of how to use a few of them; (3) an exploratory data analysis on public TE data. Finally, we are going deep to present the main challenges and possible solutions to improve resources and tools.